Aberrant methylation of Meg3 in alpha1, 3-galactosyltransferase knockout pig induced pluripotent stem cells. Issue 3 (3rd May 2016) - Kwon, Dae-Jin; Hwang, In-Sul; Kim, Hye-Rim; Kim, Yu-Ra; Oh, Keon Bong; Ock, Sun-A; Im, Gi-Sun; Lee, Jeong-Woong; Hwang, Seongsoo
ABSTRACT: Pigs have been used as a good research model for xenotransplantation. Several groups have generated porcine-induced pluripotent stem cells (piPSCs) from differentiated somatic cells. Transgenic pigs with the alpha1, 3-galactosyltransferase gene-knockout (GalT-KO) could successfully govern hyper acute rejection of organ transplants into primates. Thus, GalT-KO piPSCs could be a powerful cell resource for agricultural and biomedical applications. This study was performed to generate iPSCs from GalT-KO pigs and characterize their properties. We successfully generated a GalT-KO iPSC from a genetically modified pig using double alpha1, 3-galactosyltransferase knockout alterations. Similar to mouse embryonic stem cells, the GalT-KO piPSCs were positive for classical pluripotency markers: POU5F1, NANOG, SOX2 and SSEA1, and were negative for: SSEA3, TRA-1-60 and TRA-1-81. Furthermore, these cells could form an embryoid body that differentiated into three germ layers in vitro, and were highly proliferative under leukemia inhibitory factor culture conditions. However, the methylation status in DMR2 of the Meg3 gene was higher in GalT-KO piPSCs than in porcine ear fibroblast. In conclusion, GalT-KO piPSCs could be successfully generated by six human factors without expression of Gal-epitopes. Although aberrant methylation observed in GalT-KO piPSCs, this cell line maintained pluripotency and had differentiation properties into all three germ layers. Therefore, GalT-KO piPSCs might be a good cell source for biomedical application and basic research.